AKIBAT HUKUM HAK MEWARIS ANAK HASIL PERKAWINAN SIRI BERBASIS NILAI KEADILAN - Erni Agustina (Jurnal Pembaharuan Hukum, 2016)
Siri marriage or marriages underhand still occur in Indonesian society. Unregistered marriage is a marriage conducted in accordance with the religion or belief, just unregistered. Registration of marriage does not determine the validity of the marriage. However, registration of marriage would provide legal certainty for the husband, wife and child from the marriage. The child of a valid marriage would get their rights, including inheritance rights. Different with the children of the siri marriage, which did not obtain their rights.